A Community Partnered Approach to Promoting COVID-19 Vaccine Equity. Issue 6 (November 2021) - Scott, Taylor; Gutschow, Benjamin; Ragavan, Maya I.; Ho, Ken; Massart, Mylynda; Ripper, Lisa; Muthama, Victor; Miller, Elizabeth; Bey, Jamil; Abernathy, Rev. Paul
The coronavirus disease 2019 (COVID-19) pandemic has disproportionately affected communities of color. To dismantle these disparities, it is critical to promote COVID-19 vaccine equity, both through increasing vaccine access and addressing vaccine mistrust. This article describes a community–academic collaboration (the Community Vaccine Collaborative [CVC]), whose mission is to ensure COVID-19 vaccine equity among marginalized communities. Based in Pittsburgh, Pennsylvania, our group has focused on inclusion of marginalized groups into vaccine clinical trials, addressing vaccine mistrust, and building systems to ensuring equitable access to the COVID-19 vaccine. We review formation of the CVC, activities to-date, and recommendations for other communities interested in developing similar collaboratives.